RUMAH ULU PADA MASYARAKAT ADAT KOMERING DI OGAN KOMERING ULU TIMUR - Joko Saganta; Ali Imron; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2014)
Ulu house was a traditional house that has the function in each room. The purpose of this research was to determine the room function at the House of Komering society’s tradition in Ulu Betung Village South Sumatra. The method used was functional method. The data collection techniques were: interview techniques, observation, technical documentation, and technical literature. The technique of data analysis was the analysis of qualitative data. The results of the results shows that the House Ulu was the culture of the Komering society’s tradition which had the function of a garang, haluan, kakudan, ambin, pangking and pawon, Ulu house in maintaining the cultural values in that space of cultural value of religious/spiritual, politeness value, cooperativeness value and aesthetic value as well as having an additional function that was a function of space in the implementation of the ceremonies. Rumah Ulu sebagai rumah tradisional yang memiliki fungsi masing-masing pada tiap ruangan. Tujuannya adalah untuk mengetahui fungsi ruang pada rumah Ulu masyarakat adat komering Desa Betung Sumatera Selatan. Metodenya metode fungsional. Teknik pengumpulan datanya teknik wawancara, observasi, teknik dokumentasi, dan teknik kepustakaan. Teknik analisis data adalah analisis data kualitatif. Hasil dari penelitian Rumah Ulu adalah kebudayaan dari masyarakat adat Komering mempunyai fungsi dari garang, haluan, kakudan, ambin, pangking dan pawon, Rumah Ulu dalam menjaga nilai-nilai budayanya yakni pada ruangan tersebut memiliki nilai budaya nilai religius/keagamaan, nilai kesopanan, nilai kegotong-royongan dan nilai estetika serta memiliki fungsi tambahan yakni fungsi ruang pada pelaksanaan upacara-upacara adat. Kata kunci : masyarakat adat komering, ogan komering ulu, rumah ulu